Breastfeeding self-efficacy in terms of sleep quality, perceived social support, depression and certain variables: a cross-sectional study of postpartum women in Turkey - Dilek Konukbay; Emine Öksüz; Gulten Guvenc (BMC, 2024)
Abstract Background Breastfeeding self-efficacy is one of the key factors that affect a healthy and successful breastfeeding process. A mother's belief regarding her ability to breastfeed is influenced by social and psychological factors. This study aimed to investigate the breastfeeding self-efficacy levels of postpartum women, the factors affecting this, and its relationship with sleep quality, social support and depression. Methods This descriptive cross-sectional study was conducted in the pediatric department of a tertiary hospital in Ankara, Turkey. Data were collected from 200 postpartum women using the Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF), the Pittsburgh Sleep Quality Index (PSQI), the Multidimensional Scale of Perceived Social Support (MSPSS) and the Edinburgh Postnatal Depression Scale (EPDS). Results The mean scores of the BSES-SF, PSQI, MSPSS and EPDS were 59.05 ± 8.28, 9.18 ± 3.67, 57.82 ± 18.81, and 8.98 ± 5.89, respectively. A statistically significant negative correlation was found among the BSES-SF, EPDS (r = -0.445, p = 0.001) and PSQI (r = -0.612, p = 0.004), while a positive correlation was found among the BSES-SF, total MSPSS (r  = 0.341, p = 0.036), and family support (r  = 0.373, p = 0.014) (p < 0.05). In addition, a statistically significant difference was found between the number of births and breastfeeding self-efficacy (F = 3.68; p = 0.001). The linear regression analysis revealed that sleep quality (β = -0.491, p = 0.001), perceived social support (β = 0.146, p = 0.015), family support (β = 0.153, p = 0.013), and depression (β = -0.228, p = 0.001) emerged as the predictors of breastfeeding self-efficacy. Conclusions In this study, the increase in sleep quality and perceived social support positively affected the breastfeeding self-efficacy of postpartum women, while giving birth for the first time and an increase in the risk of depression were negatively affected.